1999
DOI: 10.4269/ajtmh.1999.60.400
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal blockage by carcinoma and Blastocystis hominis infection.

Abstract: Abstract. We detected heavy infections of Blastocystis hominis in four individuals with intestinal obstruction due to cancerous growths. After surgery, the infections spontaneously resolved, without specific chemotherapy. It appears that the B. hominis infection was coincidental and not related to the neoplastic growth. We suggest that intestinal obstruction and concomitant stool retention, plus hemorrhage from cancerous lesions, may have permitted the more abundant growth of B. hominis. This is the first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
1
8
1
1
Order By: Relevance
“…The infections in these 4 patients resolved spontaneously following surgery for the abdominal tumors. 9 The present case highlights the unusual identification of extraintestinal forms of B hominis in the abdominal fluid, confirming the clinical suspicion of intestinal perforation in this patient. To the best of our knowledge this is the first report of cytologic identification of this organism in a sample from peritoneal fluid.…”
Section: Discussionsupporting
confidence: 82%
“…The infections in these 4 patients resolved spontaneously following surgery for the abdominal tumors. 9 The present case highlights the unusual identification of extraintestinal forms of B hominis in the abdominal fluid, confirming the clinical suspicion of intestinal perforation in this patient. To the best of our knowledge this is the first report of cytologic identification of this organism in a sample from peritoneal fluid.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, Leder et al (2005) denied any correlation between clinical symptoms and B. hominis. Also, Horiki et al (1999) stated that B. hominis was not related to the occurrence of colon cancer in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms in these patients are abdominal pain, diarrhea, and flatulence [32]. One study reported an overgrowth of Blastocystis after carcinoma-induced intestinal obstruction [33]. A recent case study described Blastocystis in abdominal fluid of a patient with adenocarcinoma and associated bowel perforation [8].…”
Section: Patients With Cancermentioning
confidence: 99%